Ambient noise tomography of El Hierro island (Canary Islands) - Cabrera-Pérez, Iván; Soubestre, Jean; D’Auria, Luca; Przeor, Monika; García, Rubén; Barrancos, José; Padilla, Germán D.; Pérez, Nemesio M.; Prudencio, Janire (Frontiers in Earth Science, 2024)
El Hierro island is one of the most active islands in the Canary Islands from a volcanological point of view. This is the reason why the imaging of the internal crustal structure is of huge importance. The geophysical exploration methods employed on El Hierro Island, such as gravimetry and seismic tomography, allowed obtaining the high-resolution characterization of the crust’s deep part. However, these methods did not yield significant information about the surface and the shallower part of the crust. To gain a deeper insight into the shallow geological structure of El Hierro island, we employed Ambient Noise Tomography to construct a 3D S-wave velocity model. Our investigation revealed the presence of seven significant seismic velocity anomalies, partly identified by previous studies. We identified two high-velocity anomalies located in the eastern and western parts of the island at a depth between 0 and 3 km below sea level (b.s.l.). We interpreted these anomalies as dense intrusive complexes of dikes, possibly linked to the Tanganasoga volcano and the formation of the Tiñor edifice. Additionally, we observed two high-velocity anomalies in the northern and southern parts of the island at a depth between 3 and 4 km b.s.l., which we related to the accumulation of solidified igneous rocks. On the other hand, a low-velocity anomaly was observed in the Golfo valley, between 0 and 0.5 km b.s.l., and we interpreted it as megalandslide deposits. This anomaly was evidenced for the first time in the present study. Finally, two low-velocity anomalies were observed in the southern part of the island at different depths, between 0–0.5 km b.s.l. and 0–2 km b.s.l. These were interpreted as fractures generated by Quaternary volcanism along the SSE Rift. Also, one of them was evidenced for the first time in this study, corresponding to the zone of the fractures produced during the Quaternary volcanism. This study has allowed us to gain a more detailed understanding of the shallow geological structure of the island. Even if most of the anomalies had been evidenced previously, we could observe the existence of two low-velocity zones in the shallow crust that have not been observed before.